2019
DOI: 10.1186/s12913-019-4608-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation barriers and facilitators of an integrated multidisciplinary lifestyle enhancing treatment for inpatients with severe mental illness: the MULTI study IV

Abstract: BackgroundDespite an increase in studies showing the efficacy of lifestyle interventions in improving the poor health outcomes for people with severe mental illness (SMI), routine implementation remains ad hoc. Recently, a multidisciplinary lifestyle enhancing treatment for inpatients with SMI (MULTI) was implemented as part of routine care at a long-term inpatient facility in the Netherlands, resulting in significant health improvements after 18 months. The current study aimed to identify barriers and facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 94 publications
8
44
1
Order By: Relevance
“…First, a pitfall of current treatment is that most forensic psychiatric patients are not that motivated for their often mandatory treatment (8,9). Second, many forensic psychiatric patients experience difficulties with reflecting on their own behavior and emotions, which is an important skill for psychological treatment (10)(11)(12). Third, the forensic psychiatric patient population is extremely heterogeneous: there is no "typical" forensic psychiatric patient due to a large diversity in type of offense, mental disorders and socio-demographic background (13).…”
Section: Introductionmentioning
confidence: 99%
“…First, a pitfall of current treatment is that most forensic psychiatric patients are not that motivated for their often mandatory treatment (8,9). Second, many forensic psychiatric patients experience difficulties with reflecting on their own behavior and emotions, which is an important skill for psychological treatment (10)(11)(12). Third, the forensic psychiatric patient population is extremely heterogeneous: there is no "typical" forensic psychiatric patient due to a large diversity in type of offense, mental disorders and socio-demographic background (13).…”
Section: Introductionmentioning
confidence: 99%
“…A focus on a more contextual research approach, as in the domain of implementation science, could provide a broader view of confounding and essential aspects in the implementation of interventions in community care. In the need for a more systematic strategy towards implementation, the PRACTIS framework as proposed by Koorts et al could be an ideal framework in implementing community based interventions in a more systematic way with regard for the complexity of different contexts [ 13 , 80 , 87 ]. Evidence accentuates the possible use of digital tools in further research regarding physical health in mental healthcare [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MIDI was developed based upon a systematic review and a Delphi study among implementation experts, thereby ensuring content validity. Although psychometric properties have not yet been established, other studies in mental health administering the MIDI among health care professionals showed an internal consistency (Cronbach α) between .61-.93 [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%